Smooth muscle Acid-sensing ion channel 1a as a therapeutic target to reverse hypoxic pulmonary hypertension - Garcia, Selina M.; Yellowhair, Tracy R.; Detweiler, Neil D.; Ahmadian, Rosstin; Herbert, Lindsay M.; Gonzalez Bosc, Laura V.; Resta, Thomas C.; Jernigan, Nikki L. (Frontiers in Molecular Biosciences, 2022)
Acid-sensing ion channel 1a (ASIC1a) is a voltage-independent, non-selective cation channel that conducts both Na+ and Ca2+. Activation of ASIC1a elicits plasma membrane depolarization and stimulates intracellular Ca2+-dependent signaling pathways in multiple cell types, including vascular smooth muscle (SM) and endothelial cells (ECs). Previous studies have shown that increases in pulmonary vascular resistance accompanying chronic hypoxia (CH)-induced pulmonary hypertension requires ASIC1a to elicit enhanced pulmonary vasoconstriction and vascular remodeling. Both SM and EC dysfunction drive these processes; however, the involvement of ASIC1a within these different cell types is unknown. Using the Cre-LoxP system to generate cell-type-specific Asic1a knockout mice, we tested the hypothesis that SM-Asic1a contributes to CH-induced pulmonary hypertension and vascular remodeling, whereas EC-Asic1a opposes the development of CH-induced pulmonary hypertension. The severity of pulmonary hypertension was not altered in mice with specific deletion of EC-Asic1a (TekCre-Asic1afl/fl). However, similar to global Asic1a knockout (Asic1a-/-) mice, mice with specific deletion of SM-Asic1a (MHCCreER-Asic1afl/fl) were protected from the development of CH-induced pulmonary hypertension and right heart hypertrophy. Furthermore, pulmonary hypertension was reversed when deletion of SM-Asic1a was initiated in conditional MHCCreER-Asic1afl/fl mice with established pulmonary hypertension. CH-induced vascular remodeling was also significantly attenuated in pulmonary arteries from MHCCreER-Asic1afl/fl mice. These findings were additionally supported by decreased CH-induced proliferation and migration of pulmonary arterial smooth muscle cells (PASMCs) from Asic1a-/- mice. Together these data demonstrate that SM-, but not EC-Asic1a contributes to CH-induced pulmonary hypertension and vascular remodeling. Furthermore, these studies provide evidence for the therapeutic potential of ASIC1a inhibition to reverse pulmonary hypertension.